Getting beyond the context of French revolution in post-modern age: Striking off the partitioning of the political field on the left and right - Cvetićanin Neven (Sociološki Pregled, 2008)
The essay is dealing with the new post-modern political context that will softly get beyond, nowadays old context set by the French Revolution with all its opposites (revolution/restauration, the left/the right, republic/monarchy, red/black etc.). This new post-modern context will, instead of opposites of revolution and restoration i.e. opposites of classic left and classic right, mark opposites of extreme margin and central synthesis i.e. opposites of margin and centre, becoming the point of rotation of the political field nowadays. These new developments in political philosophy and political sociology will come on scene with series of philosophers, sociologists, politiciologies and lawthinkers who will resist to any alignment on the left, the right or the centre in its classical meaning, and the most distinctive among them will be Georges Sorel and Robert Michels, as well as, lately god deal mentioned Carl Schmitt, wherefore in this essay the attention is applied to their contribution in getting beyond the old context of French Revolution. Their opus is witnessing on how much has the era got 'beyond Left and Right' in its classical meaning, as for beyond revolution and restauration. That is also visible from some segments of the political practice after The World War II, wherefore the essay suggests model from French modern politics which got beyond the opposite of classic Left and classic Right. At the very end of the essay, controversy with tendencies of Norberto Bobbio is taken over, trying to stand up the point of view that is considering the Left and the Right essential invariables of the political life and political speech generally, that way, the final conclusion of getting beyond this classical partition of political field, is made.